2020
DOI: 10.1055/s-0040-1708456
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of a Hydroxyapatite-Based Oral Care Gel on the Calcium and Phosphorus Levels of Dental Plaque

Abstract: Objectives Particulate hydroxyapatite (HAP; Ca5(PO4)3(OH)) is a biomimetic oral care ingredient. One mode of action in caries-susceptible individuals may be the adhesion/incorporation of HAP into dental plaque. Therefore, the aim of this in vivo study was to analyze the 3-day effects of a newly developed hydroxyapatite-based oral care gel on the calcium and phosphorus levels within the dental plaque of children. Materials and Methods This study was conducted in Kebon Padangan at Bali in Indonesia. Thirty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
3
18
0
1
Order By: Relevance
“…39 Particulate HAP when adsorbed on tooth surface induce remineralization of initial caries lesions by directly filling micropores in demineralized tooth tissue, 40,41 where it acts as a crystal nucleus, and promotes crystal deposition and growth by continuously attracting large amounts of calcium and phosphate ions from the surrounding remineralization solution. 41,42 A recent study demonstrated that the HAP oral care gel tested in the present study released calcium and phosphorus on application on tooth surfaces, 26,43 thus further highlighting the potential of this gel formulation to influence remineralization and demineralization process on tooth surface. The effectiveness of fluoride in remineralizing early caries lesions in the present study once again contributed to the wealth of evidence supporting fluoride as having the most consistent benefit in preventing caries and remineralizing initial caries lesions.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…39 Particulate HAP when adsorbed on tooth surface induce remineralization of initial caries lesions by directly filling micropores in demineralized tooth tissue, 40,41 where it acts as a crystal nucleus, and promotes crystal deposition and growth by continuously attracting large amounts of calcium and phosphate ions from the surrounding remineralization solution. 41,42 A recent study demonstrated that the HAP oral care gel tested in the present study released calcium and phosphorus on application on tooth surfaces, 26,43 thus further highlighting the potential of this gel formulation to influence remineralization and demineralization process on tooth surface. The effectiveness of fluoride in remineralizing early caries lesions in the present study once again contributed to the wealth of evidence supporting fluoride as having the most consistent benefit in preventing caries and remineralizing initial caries lesions.…”
Section: Discussionsupporting
confidence: 54%
“…22 Furthermore, fluoride oral care gels seem to be more effective when acidulated, 23 thus posing the risk of erosive tooth wear if used frequently. In contrast, HAP particles interact with tooth surfaces even under neutral conditions, 13,16,24 and HAPbased toothpaste and gel has been shown to release calcium and phosphate ions in dental plaque, 25,26 hence the potential to promote remineralization and inhibit demineralization of tooth tissue. Thus, it is conceivable that the daily usage of a fluoride-free, hydroxyapatite-based oral care gel is a promising strategy to support the caries preventive effect of toothpaste.…”
Section: Introductionmentioning
confidence: 99%
“…in vivo study has shown its positive properties to release calcium in dental biofilms. 19 This can be helpful to buffer cariogenic biofilms, and with increased calcium-levels leading to a shift from tooth demineralization to remineralization. 11,17 The aim of this in vitro study was to test the whitening effect of a newly developed gel formulation based on microcrystalline HAP.…”
Section: Introductionmentioning
confidence: 99%
“… 18 A recently published in vivo study has shown its positive properties to release calcium in dental biofilms. 19 This can be helpful to buffer cariogenic biofilms, and with increased calcium-levels leading to a shift from tooth demineralization to remineralization. 11 17 …”
Section: Introductionmentioning
confidence: 99%
“…Ergänzt werden diese Arbeiten durch interdisziplinäre Grundlagenforschung und mechanistische Studien von Universitäten und Forschungseinrichtungen wie Fraunhofer-und Max-Planck-Instituten, z. B. zu den Affinitätsparametern von HAP-Partikeln und Zahnoberflächen [10,29].…”
Section: Demineralisation Und Remineralisation Des Zahnminerals/kalziunclassified